Factors Affecting the Variation of FOB Income from Ecuadorian Banana and Plantain Exports - Trujillo-Sandoval, Danny (2021)
Exports of raw materials are a fundamental source of income in Latin American countries. Banana and plantain are two of the products that Ecuador exports the most worldwide, which is why the variation in income from these items directly affects the entry of foreign currency into the national economy. The objective of this research is to determine the factors that influence this income variation through analysis and econometric decomposition of the Ecuadorian banana and plantain export time series in the period 2013-2017; as a result of the decomposition, the negative and positive peaks of the irregular component have been obtained and identified; and, these in turn have been categorized according to an analysis of the business environment, with has led to define the key factors that influence the variation in FOB income from the export of Ecuadorian bananas and plantains. The results obtained are relevant since they are an input for the institutions responsible for the generation of public policies to protect and improve the competitiveness of these products in international markets.